Influence Of Product Quality Differentiation Strategies On Client Retention In Kenya Commercial Bank Kisii Central Sub-County, Kenya - Elijah E. B. Menga; Dr. Simon Nyakwara (IJRDO - Journal of Business Management, 2020)
The Kenyan banking sector is facing stiff competition in terms of customer retention due to the increased competition in the sector. Customer retention is the goal of preventing customers from switching to the competitor. It is the way in which firms focus their efforts on existing customers in an effort to continue doing business with them. In order to retain their customers in a competitive market firms have been forced to come up with strategies that will give them competitive advantage. The purpose of the study was to assess the influence of broad differentiation strategies on client retention in Kenya Commercial Banks of Kisii Central Sub-County. The study was guided by Michael Porter’s Five Forces Theory. It adopted a descriptive survey research design with a target population of 152 employees of the Kenya Commercial banks of Kisii Central Sub-County branch. The researcher collected data using questionnaires, interviews and document analysis. The instruments were validated by the supervisors while reliability of the instruments was determined through a pilot study where any Cronbach alpha coefficients of 0.7 was attained which was considered reliable enough. Quantitative data was analyzed using descriptive and inferential (correlation) statistics, and presented in tables. The study established that product quality differentiation strategies, design differentiation strategies, product innovations differentiation strategies and brand differentiation strategies positively and significantly influence client retention.